PENGARUH PROFITABILITAS DAN STRUKTUR ASET TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (PERUSAHAAN SEKTOR INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2024) - Ummu Sholihah; Titiek Puji Astuti; Faiz Rahman Siddiq (Universitas Merdeka Madiun, 2026)
This study aims to determine the effect of capital structure, profitability, liquidity, and asset structure on firm value, with firm size as a moderating variable (industrial sector companies listed on the Indonesia Stock Exchange in 2021-2024). The data used in this study are secondary data sourced from annual reports and sustainability reports. The sampling technique used a purposive sampling method, resulting in a sample of 113 data over the four years of the study. Data analysis was performed using panel data regression using the Random Effects Model (REM) using Eviews version 12 statistical software. The results show that profitability and asset structure have an impact on firm value. Furthermore, this study also proves that firm size cannot moderate the effect of profitability and asset structure on firm value.